Pengaruh Budaya Dan Persepsi Masyarakat Non Muslim Terhadap Keputusan Menjadi Nasabah Bank Syariah Mandiri Kantor Cabang Pembantu Bengkalis - Anshor Wibowo; Nia Hariyati (JPS (Jurnal Perbankan Syariah), 2020)
This research aims to determine whether the culture and perceptions of non-Muslim communities influence the decision to become a customer at Bank Syariah Mandiri Bengkalis Sub-Branch Office partially and simultaneously. Data analysis techniques used in this study used the test of validity, reliability, hypothesis test, multiple linear regression analysis and determinant coefficient analysis. The results obtained in this study that partially cultural variables and community perceptions significantly influence the decision making to become a customer of Bank Syariah Mandiri Bengkalis Sub-Branch Office. Simultaneously there is a significant influence between culture and perceptions of non-Muslim communities on the decision to become a customer at Bank Syariah Mandiri Bengkalis Sub-Branch Office with an influence of 60.1%.